Identifikasi Morfologi Bakteri Fermentatif pada Bekasam Ikan Nila melalui Pengamatan Mikroskopis Langsung - Rifky Rifaldo Munthe; Ardi Mustakim (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Bekasam, a traditional Indonesian fermented fish product, is produced through a natural fermentation process involving complex microbial communities, particularly fermentative bacteria. These microorganisms play a vital role in developing the product’s characteristic flavor, aroma, and texture. This study aimed to identify the morphological characteristics of fermentative bacteria present in bekasam made from Nile tilapia (Oreochromis niloticus) using direct microscopic observation without staining. Fresh samples of bekasam were collected and subjected to serial dilution before being cultured on nutrient agar (NA) medium. The cultures were incubated at room temperature for 24–48 hours to allow colony formation. Morphological examination was carried out by observing the colonies directly under a light microscope to assess cell shape, size, and arrangement. The results demonstrated a diversity of bacterial morphologies, with the majority consisting of rod-shaped (bacillus) and spherical (coccus) forms. Bacillus cells were often observed singly or in short chains, whereas coccus cells appeared either as single units, in pairs (diplococci), or forming short chains (streptococci). The morphological diversity observed suggests that multiple bacterial species may be involved in the fermentation process, each contributing differently to biochemical transformations such as protein degradation, lactic acid production, and flavor compound formation. Although morphological characterization alone cannot provide definitive bacterial identification, these findings serve as preliminary data for subsequent microbiological and molecular analyses. Further research using biochemical tests and molecular approaches, such as 16S rRNA gene sequencing, is recommended to confirm species identity and to explore their specific roles in fermentation. Understanding the microbial composition of bekasam can provide valuable insights for optimizing fermentation conditions, improving product consistency, and ensuring safety in traditional fish-based fermented foods.